2023
DOI: 10.1177/22799036231152327
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and determinants of self-medication practices among general population: A cross-sectional study in Thimphu, Bhutan and Chattogram, Bangladesh

Abstract: Background: Self-medication is a global phenomenon and a potential contributor to negative health consequences on human health including emergence of antibiotic drug resistance globally. Objective: The primary objective of this study was to estimate the prevalence and determinants of self-medication in Thimphu, Bhutan and Chattogram, Bangladesh, two neighbouring South Asian country. Methodology: A community-based cross-sectional study was conducted in the city of Thimphu, Bhutan and Chattogram, Bangladesh. A p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…7 Among the adult population of Bangladesh, it was reported that about 41.5% and 61.8% were involved in the practice from studies in Chattogram and Thimphu, respectively. 8 Participants from these two cities cited lack of perceived seriousness of the disease and no hospitals in nearest places as reasons for self-medication. 8 In Nigeria, while about 41% of the population was reported to be involved in self-medication during the COVID-19 pandemic, the commonest reason for self-medication was fear of stigmatization and discrimination.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 Among the adult population of Bangladesh, it was reported that about 41.5% and 61.8% were involved in the practice from studies in Chattogram and Thimphu, respectively. 8 Participants from these two cities cited lack of perceived seriousness of the disease and no hospitals in nearest places as reasons for self-medication. 8 In Nigeria, while about 41% of the population was reported to be involved in self-medication during the COVID-19 pandemic, the commonest reason for self-medication was fear of stigmatization and discrimination.…”
Section: Introductionmentioning
confidence: 99%
“… 8 Participants from these two cities cited lack of perceived seriousness of the disease and no hospitals in nearest places as reasons for self-medication. 8 In Nigeria, while about 41% of the population was reported to be involved in self-medication during the COVID-19 pandemic, the commonest reason for self-medication was fear of stigmatization and discrimination. 9 This has been attributed to increased uncontrolled availability of drugs usage without prescription in these countries.…”
Section: Introductionmentioning
confidence: 99%
“…Worldwide, it ranges from 11.7% to a staggering 92%. In developing nations, this practice is even more widespread, with rates ranging from 12.7-95%, while in Western countries, it is comparatively lower, often reported at around 3% (2,3).…”
mentioning
confidence: 99%
“…In India, self-medication is a widespread phenomenon, affecting both urban and rural populations. Approximately 37% of individuals in urban areas and 17% in rural areas engage in self-medication practices (3). Alarmingly, more than half of the adolescent population in India, exceeding 50%, resort to self-medication daily.…”
mentioning
confidence: 99%
See 1 more Smart Citation